Assisted Bioremediation by Bacillus sp.: Impact on the Growth of Vicia faba L. under Copper Contamination Conditions: RESEARCH PAPER - Abdelhakim Sellal; Rima Belattar; Amor Bencheikh; Mondher Fradjia; Nora Laouicha (Annals of Arid Zone, 2025)
Under greenhouse conditions stem length, branching, leaf area, and total chlorophyll content of Vicia faba plants grown in copper-contaminated soil were similarly improved by both EDTA (positive control) and Bacillus sp. treatments. Stem height at flowering and maturation stages was slightly higher in Bacillus sp.–treated plants (35.33 ± 1.52 cm and 46.33 ± 1.52 cm) than in EDTA-treated plants (34.33 ± 3.51 cm and 44.00 ± 5.56 cm), although the difference was not statistically significant. Branching and leaf area followed a comparable trend, with both treatments showing higher values than the negative control, but no significant differences between them. Total chlorophyll content was consistently higher in both treatments compared with copper-stressed plants, with minor fluctuations over time, indicating partial protection of the photosynthetic system. Overall, these results suggest that Bacillus sp. inoculation provides a bioremediation effect comparable to EDTA, promoting growth and mitigating copper toxicity through biologically mediated mechanisms.